Hakekat Dan Aplikasi Kaidah Fiqih Tafriq Al-Halal ‘An Al-Haram (Idza Ijtama’ Al-Halal Wa Al-Haram Ghuliba Al-Haram) - Hudzaifah Achmad Qotadah (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
This article aims to discuss the principles of fiqhiyyah at-tafriq baina al-halal wal haram (separation between something halal and haram). The rule that is the subject of study is the rule, namely the rule